Integrasi Pendidikan Agama Islam dengan Literasi Digital untuk Membentuk Generasi Berakhlak Mulia di MI Miftahul Ulum - Syahda, Latifa (Lembaga Riset dan Inovasi Almatani, 2026)
Technological developments in the modern era require the world of education to adapt without neglecting moral and religious values. The integration of Islamic Religious Education (PAI) with digital literacy is a crucial effort in developing students who are not only technologically proficient but also possess noble character. This study aims to describe and analyze the implementation of PAI integration with digital literacy at MI Miftahul Ulum as a means of developing students' noble character. The research method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results indicate that the integration of PAI with digital literacy was implemented through the use of Islamic-themed digital learning media, religious-themed digital literacy activities, and the instilling of media ethics in accordance with Islamic values. This integration has a positive impact on student character development, marked by increased discipline, responsibility, and politeness in daily life and digital activities.